Sea Guidelines. A Comparative Analysis: First Outcomes - De Montis, Andrea; Ledda, Antonio; Caschili, Simone; Ganciu, Amedeo; Barra, Mario; Cocco, Gianluca; Marcus, Agnese (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The European Directive 2001/42/EC (Directive) has introduced the Strategic Environmental Assessment (SEA), a procedure for assessing the effects of certain plans and programs on the environment. The Directive has been transposed in different ways and times within Europe: member states have frequently drawn up guidelines to facilitate SEA implementation, by adopting different approaches. So far a few studies have been performed to analyze SEA guidelines. In this paper we aim to analyze key elements of SEA guidelines released by seven European countries in order to evaluate the effectiveness of those documents and SEA implementation. We have found that no SEA guidelines satisfy all key elements we have identified. Based on the latter finding, this work is introductory to a further analysis which aims to characterize SEA guidelines and define a proposal of SEA guidelines for landscape planning in the Italian region of Sardinia.